Pengaruh Fasilitas Terhadap Kepuasan Wisatawan Di Curug Pangeran, Kawasan Gunung Salak Endah, Kabupaten Bogor - Samuel Samuel; Riani Ishak (LPPM Universitas Dinamika Bangsa, 2023)
This research was conducted aiming to determine the effect of facilities on tourist satisfaction at Curug Pangeran, Mount Salak Endah Area, Bogor Regency. This study uses a quantitative approach method. The data analysis method used in this study is simple linear regression analysis because it uses 2 variables, namely facilities as the X variable and tourist satisfaction as the Y variable. The tool used in this research is SPSS version 24.0 to find out how much influence the variable has. X to variable Y. The sampling technique in this study used non-probability sampling with a purposive sampling technique and by using a questionnaire. The sample used in this research is Curug Pangeran tourists, Mount Salak Endah area, Bogor Regency with 100 respondents. Based on the test results obtained a significance value of 0.000 which is smaller than 0.05. Then the correlation value of the relationship between facilities (X) to tourist satisfaction (Y) is obtained of 0.642 which is included in the strong category. Based on this, the facilities have a significant and positive effect on tourist satisfaction at Curug Pangeran, Mount Salak Endah Area, Bogor Regency.